2022
DOI: 10.21470/1678-9741-2021-0088
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Immature Granulocytes as A Prognostic Factor in ST-Elevation Myocardial Infarction

Abstract: Objective ST-segment elevation myocardial infarction (STEMI) is a serious, life-threatening disease. Inflammatory markers have recently become the focus of attention in the assessment of severity in the early stages of STEMI. This study aimed to evaluate the importance of immature granulocytes (IG) as a prognostic marker in STEMI. Methods Patients admitted to the coronary care unit with a diagnosis of STEMI and who underwent primary percutaneous coronary intervention (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In several studies, IG is an important biomarker in predicting short-term mortality in patient groups. 6,7 However, as far as we know, there is no study todate in the literature on IG in long-term mortality. We think that our study is the first study on this aspect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, IG is an important biomarker in predicting short-term mortality in patient groups. 6,7 However, as far as we know, there is no study todate in the literature on IG in long-term mortality. We think that our study is the first study on this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, Korkut et al found the mortality rates in STelevation myocardial infarction to be significantly higher in the high IG group compared to the low IG group. 7 Moreover, Korkut et al found that high IG levels were significantly associated with 30-day mortality in AIS. 5 Our study showed a statistically significant correlation between high IG value and short-term mortality in cases with AIS.…”
Section: Discussionmentioning
confidence: 99%
“…The European Research Journal Volume 9 Issue 2 March 2023 tion [21]. In addition, troponin, CRP, and NLR were used both in clinical scoring and as prognostic indicators [22]. NLR is one of the parameters that have been published in many articles in recent years to predict shortand long-term mortality in patients with STEMI and NSTEMI [23][24][25].…”
mentioning
confidence: 99%